ANALISIS IMPLEMENTASI KEBIJAKAN UPAH MINIMUM DI KARAWANG PASCA PENGHAPUSAN UMSK DALAM PERSPEKTIF SERIKAT PEKERJA - Tino Kurnia (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the implications of the absence of Sectoral Minimum Wages for District/City (UMSK) in the wage policy of Karawang Regency following the enactment of the Omnibus Law on Job Creation. The sectoral minimum wage policy was abolished through the Omnibus Law on Job Creation along with its derivative regulations, which altered the wage policy by eliminating UMSK and introducing new provisions and calculations for minimum wage determination. This research uses a qualitative method with a comparative legal approach, focusing on the perspective of trade unions in Karawang Regency. Data were collected through interviews and the study of relevant documents. The findings indicate that the loss of UMSK has resulted in a reduction in workers' bargaining power in certain sectors, wage policies that do not take into account the business sector and company conditions, and a decrease in protection for workers in regions that previously had UMSK. This study provides an overview of the implementation of wage policies after the Job Creation Law and offers solutions related to the protection of workers in certain sectors.